TEACHERS’ PERCEPTION OF STUDENTS’ READINESS IN THE IMPLEMENTATION OF THE 21ST-CENTURY SKILLS IN PRIVATE PRIMARY SCHOOLS - Balqis, Putri; Padmadewi, Ni Nyoman; Dewi, Ni Luh Putu Eka Sulistia; Artini, Luh Putu (International Journal of Language and Literature, 2020)
This research was examined the teachers’ readiness for the implementation of 21st century skills in teaching English in private primary schools in Buleleng. The research was done in North Bali Bilingual School and SD Mutiara. The respondents involved in this research were 15 respondents. There were English teachers, teachers who use English as the medium of instruction, and the headmaster of the schools was becoming the research subject. The teachers’ readiness were analyzed from perceived readiness and observed readiness. However, this article focused on the teachers’ perception of students’ readiness in the implementation of 21st century skills. The results of this research represented how the teachers understand the usage skills in implementing the 21st century skills. The results of this present research indicated that the students from private primary schools were ready to apply to 21st century skills.